Effect of sales growth, capital intensity and debt to equity ratio on tax avoidance as moderated by firm size - Peter Winarta; Matondang Elsa Siburian; Enda Noviyanti Simorangkir; Wilsa Road Betterment Sitepu (International Journal of Academe and Industry Research)
This study aims to analyze the effect of sales growth, capital intensity, and debt to equity ratio on tax avoidance with firm size as a moderating variable. This quantitative research focused on seventeen food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Data were analysed using Structural Equation Modelling with a Partial Least Square approach. The findings revealed that sales growth and debt to equity ratio do not significantly impact tax avoidance, while capital intensity does. Additionally, firm size does not moderate the relationship between sales growth or debt to equity ratio and tax avoidance but strengthens the effect of capital intensity on tax avoidance. These results offer valuable insights for financial management within the sector, highlighting the importance of strategic asset management in reducing tax burdens. The study’s findings suggest that regulators may need to refine tax policies to address the nuanced effects of capital investment on tax avoidance behaviors, especially in large firms.